Benzimidazole‐carbamate anthelmintics: Perspective candidates for the anticancer drug development. Issue 2 (16th March 2022) - Prasher, Parteek; Sharma, Mousmee
Abstract: Cellular oncogenesis involves a complex interplay between the several synchronized, interdependent pathways that collectively determine the pathogenesis and pathophysiology of cancer. Limited therapeutic success with the existing anticancer drugs drew huge interest in the design and development of new pharmacophores with improved clinical efficacy, however despite huge investments in anticancer RD; the average number of Food and Drug Administration‐approved anticancer drugs declined since the 1990s. The contemporary anticancer medications possess high attrition rates, bear substantial costs, and experience low efficacy owing to the drug resistance expressed by the aggressive tumors. Mainly, the translation of novel candidate anticancer drugs into clinical practice, their commercialization, and transformation from the bench to bedside require a long timeframe of 10–15 years and capital worth millions of dollars. The repurposing strategy substantially accelerated the anticancer drug development regime as the approved drugs with tested safety and efficacy ensure a minimal risk of failure, and nominal R&D expenses as anticipated for the newly identified candidate drugs yet to enter the clinical trials. In addition, the repurposed drugs ensure a rapid clinical translation due to a validated clinical profile and their ability to target the identified hallmarks and hitherto unknown vulnerabilities of cancer. The flagship project "Repurposing Drugs in Oncology" (ReDO) identified 268 "hard repurposing" noncancer medications as candidate drugs with a promising anticancer profile (https://www.anticancerfund.org/en/redo-db ). However, the generic profile of 84% of repurposed drugs in ReDO data set discourages the commercial sponsors from funding the repurposing trials, especially the Phase III efficacy trials that require significant capital.